Early Convalescent Plasma Therapy and Mortality Among US Veterans Hospitalized With Nonsevere COVID-19: An Observational Analysis Emulating a Target Trial. (21st June 2021) - Cho, Kelly; Keithly, Sarah C; Kurgansky, Katherine E; Madenci, Arin L; Gerlovin, Hanna; Marucci-Wellman, Helen; Doubleday, Annie; Thomas, Eva R; Park, Yojin; Ho, Yuk-Lam; Sugimoto, Jonathan D; Moore, Kathryn P; et al.
Abstract: Background: Early convalescent plasma transfusion may reduce mortality in patients with nonsevere coronavirus disease 2019 (COVID-19). Methods: This study emulates a (hypothetical) target trial using observational data from a cohort of US veterans admitted to a Department of Veterans Affairs (VA) facility between 1 May and 17 November 2020 with nonsevere COVID-19. The intervention was convalescent plasma initiated within 2 days of eligibility. Thirty-day mortality was compared using cumulative incidence curves, risk differences, and hazard ratios estimated from pooled logistic models with inverse probability weighting to adjust for confounding. Results: Of 11 269 eligible person-trials contributed by 4755 patients, 402 trials were assigned to the convalescent plasma group. Forty and 671 deaths occurred within the plasma and nonplasma groups, respectively. The estimated 30-day mortality risk was 6.5% (95% confidence interval [CI], 4.0%–9.7%) in the plasma group and 6.2% (95% CI, 5.6%–7.0%) in the nonplasma group. The associated risk difference was 0.30% (95% CI, −2.30% to 3.60%) and the hazard ratio was 1.04 (95% CI, .64–1.62). Conclusions: Our target trial emulation estimated no meaningful differences in 30-day mortality between nonsevere COVID-19 patients treated and untreated with convalescent plasma. Clinical Trials Registration. NCT04545047. Abstract : This study used electronic health record data to emulate a target trial of early COVID-19 convalescent plasma and 30-day mortality risk. No differences in mortality risk were found between patients with nonsevere COVID-19 who were treated and untreated with plasma.